Hybrid method for numerical simulation of room acoustics: part 2 - validation of the computational code RAIOS 3 - Tenenbaum,Roberto A. (2007)
In the companion paper "Hybrid method for numerical simulation of room acoustics with auralization: Part 1- Theoretical and numerical aspects" a new hybrid method for numerical simulation of room acoustics, implemented by the software RAIOS 3, was presented. Here, the software itself and its main features are discussed. It will be shown that the proposed method actually results in very reliable and accurate predictions of the main acoustical parameters: T30, EDT, C80, D50, TS, G, LF and LFC. The performance of RAIOS 3 was assessed in an international intercomparison, coordinated by the Physikalisch-Technische Bundesanstalt, in Germany, where measured acoustical parameters where compared to those predicted by 9 different software. Due to the hybrid method proposed, the comparative results shown a very good agreement between the parameters predicted by our software and the measurements, even in a somewhat diffuse condition. In a statistical evaluation, the results obtained by the numerical code RAIOS 3, stayed among the top 10%. The strong dependency of the predicted acoustical parameters on reliable room data, especially absorption and diffusion coefficients, is also discussed.